Hyperuricemia as an Additional Risk Factor for Coronary Artery Disease: A Hospital Based Case Control Study in Western Region of Nepal - Mittal, Ankush; Sathian, Brijesh; Kumar, Arun; Chandrasekharan, Nishida; Farooqui, Shamim Mohammad; Singh, Shailendra; Yadav, Shambhu Kumar (Nepal Journal of Epidemiology, 2011)
Background In the 21st century, cardiovascular diseases will continue to dominate the disease spectrum and death statistics in both the industrialized and developing worlds. Coronary artery disease (CAD) is the foremost cause of cardiovascular disease related deaths worldwide, with >4.5 million deaths taking place in the developing world. Augmented serum uric acid levels are recurrently come across with hyperlipidemia, atherosclerosis, obesity, glucose intolerance, renal disease, and hypertension which all play a fundamental role in the pathogenesis of coronary artery disease. Materials and methods It was a hospital based case control study carried out in the Department of Biochemistry of Manipal Teaching Hospital, Pokhara, Nepal between 1st January 2010 and 31st December 2010. The variables collected were age, gender, serum uric acid, total cholesterol, low density lipoproteins, triglycerides, high density lipoproteins and very low density lipoproteins. Approval for the study was obtained from the institutional research ethical committee. Results There was insignificant difference for age between groups. In cases of hyperuricemia, there was marked increase in levels of serum uric acid (8.043± 0.43 mg/dl) when compared to controls (4.28 ± 0.66 mg/dl. In patients suffering from coronary artery disease with hyperuricemia, there was marked increased in levels of serum uric acid(8.222 ± 0.39 mg/dl) found to be statistically significant when compared to controls (4.285 ±0.66 mg/dl) and values were quite similar to hyperuricemic patients (8.043 ± 0.43 mg/dl).Further, in patients suffering from coronary artery disease with hyperuricemia, there was marked increased in mean values of serum total cholesterol (257.56 ± 22.65 mg/dl) ) when compared to controls (173.22 ± 32.63mg/dl). Conclusion Hypercholesterolemia due to hyperuricemia is most common modifiable factor for coronary artery disease. Allopurinol and newer urate-lowering agents restores endothelial function in coronary artery disease patients. The ability of physicians to pharmacologically manage serum urate levels, a better understanding of the interaction between hyperuricemia, gout and vascular disease may be critical for the reduction of morbidity and mortality in high-risk coronary artery disease patients. Key words: Hyperuricemia; Coronary artery disease; Nepal DOI: http://dx.doi.org/10.3126/nje.v1i3.5571 Nepal Journal of Epidemiology 2011;1(3) 81-85